Libraries in the Spotlight: First Amendment Auditors and Social Media Commentary - Mann, Jasvinder (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2025)
Social media platforms have amplified public scrutiny of libraries, as First Amendment auditors (FAAs) record their interactions to test constitutional boundaries. These encounters spark debates over the balance between free speech and maintaining an inclusive, orderly environment. Through an analysis of 300 YouTube comments on FAA-library interactions, this study highlights polarized public reactions influenced by selective video editing and algorithm-driven echo chambers. While auditors bring attention to issues of transparency, their confrontational tactics often challenge the core mission of libraries. The findings emphasize the importance of clear policies, staff training, and strategies to address the complexities of digital accountability. Les bibliothèques sous les projecteurs: auditeurs du Premier amendement et commentaires sur les médias sociaux Résumé Les plateformes de médias sociaux ont amplifié l'examen public des bibliothèques, car les auditeurs du Premier amendement enregistrent leurs interactions pour tester les limites constitutionnelles. Ces rencontres suscitent des débats sur l'équilibre entre la liberté d'expression et le maintien d'un environnement inclusif et ordonné. Grâce à l'analyse de 300 commentaires YouTube sur les interactions entre les auditeurs et les bibliothèques, cette étude met en lumière les réactions polarisées du public qui sont influencées par le montage de vidéo sélectif et les algorithmes. Alors que les auditeurs attirent l'attention sur les questions de transparence, leurs tactiques de confrontation remettent souvent en question la mission principale des bibliothèques. Les résultats soulignent l'importance de politiques claires, de formation du personnel et de stratégies pour adresser les complexités de la responsabilité numérique.